Distributed current control for multi-three phase synchronous machines in fault conditions - Galassini, Alessandro; Costabeber, Alessando; Degano, Michele; Gerada, C.; Tessarolo, A.; Castellan, S. (2016)
Among challenges and requirements of on-going electrification process and future transportation systems there is demand for arrangements with both increased fault tolerance and reliability. Next aerospace, power-train and automotive systems exploiting new technologies are delving for new features and functionalities. Multi-three phase arrangements are one of these novel approaches where future implementation of aforementioned applications will benefit from. This paper presents and analyses distributed current control design for asymmetrical split-phase schemes composed by symmetrical three phase sections with even number of phases. The proposed design within the dq0 reference frame in nominal, open and short circuit condition of one three-phase system is compared with the vector space decomposition technique and further validated by mean of Matlab/Simulink ~R simulations.